Gemeentegrense, nuwe gemeente ontwikkeling en kerkverband in die Nederduitse Gereformeerde Kerk - Celliers, A. (Acta Theologica, 2006)
In this article it is argued that in any system in which membership of a particular congregation is determined by the members themselves through subjective criteria, the relationship between congregations is influenced detrimentally. Subjective criteria are the opposite of objective criteria such as geographical boundaries or different language groups. The same is true when a congregation is not respected as God’s complete church. Beside this, subjective criteria also question God’s providence and also the essential variety of God given gifts that should be present in the congregation in order to function as a complete and healthy Body of Christ. New church development has to take all this into consideration when churches for different culture and generation groups are planted within the borders of existing congregations. It is, after all, not context that is the norm for the church, but God Himself through his Word and Spirit.